Preliminary trajectory design for NASA's Solar Cruiser: A technology demonstration mission. (June 2021) - Pezent, James B.; Sood, Rohan; Heaton, Andrew; Miller, Kyle; Johnson, Les
Abstract: This investigation outlines preliminary trajectory design for NASA's sail-based Solar Cruiser spacecraft, selected on December 3, 2020, to be a secondary payload launched with the Interstellar Mapping and Acceleration Probe (IMAP) in 2025. Trajectory optimization is carried out to ensure that Solar Cruiser can successfully reach a halo orbit about a Sun–Earth sub- L 1 Lagrange point in under one year using only solar sail propulsion. Trade studies are performed to identify optimal trajectories subject to restrictions on sail incidence angles and deployment times, and off nominal initial-conditions are examined to determine the feasibility of the baseline mission profile. Results, thus far, show that Solar Cruiser can be incorporated as a secondary payload on IMAP while satisfying tight operational restrictions. However, additional work must be done to mitigate risks from large launch vehicle injection errors. Highlights: Solar Cruiser is a sail-based technology demonstration mission under development at NASA Marshall Space Flight Center. Solar Cruiser will share a ride to space in 2025 with the Interstellar Mapping and Acceleration Probe (IMAP). For the given launch vehicle constraints, Solar Cruiser can successfully transfer to a sub-L1 halo orbit. Limited sail maneuvering required with an appropriately timed sail-deployment.